In Memory of Dr Hei Leung - Zeigler, Robert S. (Springer, 2022)
The rice world lost a much-loved friend and intellectual light with the passing of Hei Leung. Hei was a passionate scientist and caring mentor who dedicated his professional life to rice research and to helping younger colleagues grow in their professions. He played key roles in numerous endeavors from his position at the International Rice Research Institute (IRRI), contributing to new understandings of the rice genome and to rice blast research. In addition to his many research contributions, Hei provided leadership in the international community to build and distribute rice genetic and genomic resources and contributed to strengthening research capacity in plant pathology in Asia and beyond. Hei brought a distinctive joy, energy and enthusiasm to science, volleyball and friendship and will be greatly missed.